'Proper' pro-nun-ʃha-ʃhun in Eighteenth-Century English: ECEP as a New Tool for the Study of Historical Phonology and Dialectology. (21st March 2017) - Yáñez-Bouza, Nuria; Beal, Joan C; Sen, Ranjan; Wallis, Christine
Abstract: English historical linguists have often complained about the scholarly neglect of the phonology of the Late Modern English period; yet, the value of pronouncing dictionaries as rich and reliable evidence has been demonstrated (Beal, J. C., 1999, English Pronunciation in the Eighteenth Century: Thomas Spence's Grand Repository of the English Language (1775) . Oxford: Clarendon Press; Jones, C., 2006, English Pronunciation in the Eighteenth and Nineteenth Centuries. Basingstoke: Palgrave Macmillan). This article presents a new electronic, searchable database of 'Eighteenth-Century English Phonology' (ECEP) which aims to facilitate research on the social, regional, and lexical distribution of phonological variants in 18th-century English, as documented in contemporary pronouncing dictionaries. Taking Wells' (1982, Accents of English . Cambridge: Cambridge University Press) lexical sets for the vowel system of present-day varieties of English as its reference, the database provides unicode IPA transcriptions for the relevant segment of each word given as an example of lexical (sub)set in his account of standard lexical sets, to which we have added some complementary consonant sets. These will be of use for comparative studies with 19th-century and present-day English. First, we describe the methodology and contents of ECEP: primary source selection, data input and annotation, the web-based interface. Second, we report on two case studies that demonstrate the value of evidence that can be systematically extracted from ECEP for the analysis of segmental and suprasegmental phonology; these are variations in the pronunciation of 'wh' in the set whale (/hw/∼/w/∼/h/), and the palatalization of alveolar consonants before /uː/. Thus, this article will demonstrate the viability of ECEP for historical phonology, dialectology, and sociolinguistics, and will help to promote the use of databases as key resources in historical linguistics.